Biodiversity in a changing climate: a synthesis of current and projected trends in the US. Issue 9 (1st November 2013) - Staudinger, Michelle D; Carter, Shawn L; Cross, Molly S; Dubois, Natalie S; Duffy, J Emmett; Enquist, Carolyn; Griffis, Roger; Hellmann, Jessica J; Lawler, Joshua J; O'Leary, John; Morrison, Scott A; Sneddon, Lesley; et al.
Abstract : This paper provides a synthesis of the recent literature describing how global biodiversity is being affected by climate change and is projected to respond in the future. Current studies reinforce earlier findings of major climate‐change‐related impacts on biological systems and document new, more subtle after‐effects. For example, many species are shifting their distributions and phenologies at faster rates than were recorded just a few years ago; however, responses are not uniform across species. Shifts have been idiosyncratic and in some cases counterintuitive, promoting new community compositions and altering biotic interactions. Although genetic diversity enhances species' potential to respond to variable conditions, climate change may outpace intrinsic adaptive capacities and increase the relative vulnerabilities of many organisms. Developing effective adaptation strategies for biodiversity conservation will not only require flexible decision‐making and management approaches that account for uncertainties in climate projections and ecological responses but will also necessitate coordinated monitoring efforts.